Meningkatkan Penjualan Online UMKM Desa Temuroso Demak dengan Digital Marketing - Anik, Sri; Wasitowati, Wasitowati; Gulnoria, Revy Amyneva (Indonesian Journal of Community Services, 2024)
Temuroso is a village in Guntur, Demak, Central Java. Several community members in Temuroso have created entrepreneurs with different types of businesses, namely: fashion, culinary, trade, handicrafts, food, and drinks. Since Covid-19, many domestic and global economic sectors have been affected. The impact of this pandemic is being felt by MSMEs sector. The decline in MSME and cooperative turnover due to COVID-19 is very significant. Therefore, MSME actors in Temuroso need to be given training related to digital marketing so they can market their products online so as to further improve sales performance. The implementation of community service for digital market training in Temuroso was carried out comprehensively, starting from introducing digital marketing through the Shopee marketplace, uploading products, and registering for free shipping. This training was attended by 20 out of 79 UMKM actors, especially those who were very familiar with gadgets and digitalization, guided by competent resource persons. In the digital marketing training, only 20% succeeded in creating an account on the Shopee marketplace and uploading their products, this showed that digital marketing training for business actors (MSMEs) is able to improve sales performance because MSME products are better known to the wider community. Furthermore, this digital marketing training is expected to improve the welfare of MSMEs in Temuroso, Guntur, Demak, Central Java. This digital market training can have an impact on increasing sales and will further improve sales performance and welfare of MSMEs in Temuroso village, Guntur, Demak, Central Java.